Adaptive Sliding Mode Based Fault Tolerant Consensus Control for Multi-agent System - GE Zhiwen; LIU Jianwei; WANG Yifan (Kongzhi Yu Xinxi Jishu)
It presented an algorithm of adaptive sliding mode based fault tolerant consensus control for multi-agent systems, in the presence of external disturbance and actuator faults simultaneously. Firstly, the directed network topology is introduced to describe the information exchange among multi-agent. Secondly, the discontinuous control protocol based on integral sliding mode is introduced. Then, an adaptive sliding mode fault tolerant consensus control scheme is designed to deal with the external disturbance, actuator fault and the chattering problem caused by discontinuous control. Finally, the effectiveness and superiority of the proposed scheme is demonstrated by the numerical simulation results based on unmanned quadrotor helicopter.